1990
DOI: 10.1577/1548-8667(1990)002<0012:aaapbp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Antiviral Agent (46NW-04A) Produced byPseudomonassp. and Its Activity against Fish Viruses

Abstract: Abs/raa.-The antiviral agent 46NW·04A was isolated and characterized from cell-free culture fluid of PseutiomofUJS sp. 46NW.Q4 isolated fro m the aquatic environment. Production of the antiviral substance was muimal at 25"C during days 2-3 of bacterial incubation. Extraction from )0 L of culture fluid by ethyl acetate and purification by thin-layer chromatography on silica gel resulted in 709 mg of the purified antiviral material. Molecular weight of this substance was 1, 126 by secondary ionization mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The activity of tributylamine, chloroquine and amantadine as antiviral agents has been observed for mammalian viruses at very early stages of infection. For fish viruses, very few studies have focused on chemotherapy (Migus & Dobos 1980; Kimura, Yoshimizu, Ezura & Kamei 1990; Micol, Caturla, Pérez‐Fons, Más, Pérez & Estepa 2005) and little is known about inhibition in the early stages of infection. Our results indicated that IHNV is the most sensitive of the three viruses tested to the action of lysosomotropic compounds which block binding.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of tributylamine, chloroquine and amantadine as antiviral agents has been observed for mammalian viruses at very early stages of infection. For fish viruses, very few studies have focused on chemotherapy (Migus & Dobos 1980; Kimura, Yoshimizu, Ezura & Kamei 1990; Micol, Caturla, Pérez‐Fons, Más, Pérez & Estepa 2005) and little is known about inhibition in the early stages of infection. Our results indicated that IHNV is the most sensitive of the three viruses tested to the action of lysosomotropic compounds which block binding.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the antiviral activity of a peptide purified from Pseudomonas culture supernatants was thought to prevent the adsorption of virus particles on to host cells by changing the viral morphology or coating the virus surface. Reactivity was particularly strong against enveloped viruses (Kimura et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…(Kimura et al . ) or cecropin B peptide was reported (Chiou et al . ), while some plant‐derived compounds have also been shown to inhibit the infectivity of viral septicaemia haemorrhagic virus (VHSV) in vitro (Micol et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently an antiviral substance produced by Pseudomonas fluorescens 46 NW-04, one of the 126 strains, was purified and identified as a peptide (Kamei et al, 1988c(Kamei et al, , 1992Kimura et al, 1990).…”
mentioning
confidence: 99%